2010
DOI: 10.2217/whe.10.39
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in Reproductive Medicine

Abstract: Acupuncture is increasingly being used in reproductive medicine. This review summarizes the evidence of acupuncture in pain relief for oocyte retrieval, improving pregnancy outcomes of in vitro fertilization treatment, management of ovulation disorders, male subfertility, primary dysmenorrhea, endometriosis and menopausal symptoms. However, most of the studies are nonrandomized uncontrolled trials, case reports or case series. For randomized controlled trials, the sample size is underpowered and blinding of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Instead, we focused on symptomatic improvement. Acupuncture is widely used and has been studied as treatment for several chronic medical conditions, from migraines 27 and pelvic pain syndromes such as dysmenorrhea28, 29 to urinary incontinence 9 and fertility issues, 30 with improvement in patient symptoms. Similarly, we noted improvement in our subjects' symptoms, primarily that of low sexual desire.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we focused on symptomatic improvement. Acupuncture is widely used and has been studied as treatment for several chronic medical conditions, from migraines 27 and pelvic pain syndromes such as dysmenorrhea28, 29 to urinary incontinence 9 and fertility issues, 30 with improvement in patient symptoms. Similarly, we noted improvement in our subjects' symptoms, primarily that of low sexual desire.…”
Section: Discussionmentioning
confidence: 99%
“…Semen Quality Improvement effects of acupuncture in infertile men. [4][5][6] Although the majority of previous studies are based on uncontrolled trials, they suggest that acupuncture improves sperm count, 10 sperm motility, 7 and sperm morphology. 11 We identified acupuncture points based on the acupuncture studies reported above and used electrical stimulation on acupoint ST29 to maximize the effectiveness of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although the mechanism by which acupuncture improves semen quality is unknown, it is possible that acupuncture might enhance blood supply in the testicular arteries, decrease testicular temperature, and stimulate systemic immune-regulatory actions. 6 Cervi Pantotrichum Cornu pharmacopuncture has been used to regulate the kidney yin and yang in TKM. The extracts also display antioxidant and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations